Measuring Productivity of Some Selected Dairies of Kathmandu Valley - Bhandari, Shankar Prasad (Economic Journal of Development Issues, 2010)
With the starting of twenty first century many business enterprises are facing the problem of quality products, cost reduction, and customers' satisfaction. Because of a high competitive and complex business environment, productivity improvement has become the most important issue in the context of liberalization and globalizes economies. With the objective of assessing and analyzing the productivity of some selected dairies established in Kathmandu valley, secondary data of concerned dairies have been collected from the annual audited financial statements and other published documents. Data are analysed by applying chi-square test, rank correlation coefficient, mean value, standard deviation and coefficient of variation. It is found that the overall productivity trend line of Dairy Development Corporation (DDC), Himalayan Dairy Products Pvt. Ltd (HDP) and Bhaktapur Dairy Pvt. Ltd (BDP) revealed an upward movement with positive growth rate while the Kathmandu Dairy Pvt. Ltd (KDP) and Integrated Dairy and Agro. Pvt. Ltd (IDAP) revealed negative growth pattern. No single productivity measurement technique is likely to give a complete picture of the performance of an organization. Key words: Dairy firms; Kathmandu; Human resource; Overhead; Productivity ratio; Productivity trend Economic Journal of Development Issues Vol. 9 and 10 (2008 & 2009) Combined Issue Page: 102-114